Understanding recent trends in income inequality in the People's Republic of China - Juzhong Zhuang; Li Shi (Asian Development Bank (ADB), 2016)
This paper examines underlying factors that could explain the decline in income inequality in the People's Republic of China (PRC) since 2008 and inquires whether the decline indicates that the PRC's income inequality has peaked following the Kuznets hypothesis. The paper first identifies four key drivers of rising income inequality in the PRC since the mid-1980s: rising skill premium, declining share of labor income, increasing spatial inequality, and widening inequality in the distribution of wealth. It then provides evidence that the reversal of these drivers, with the exception of wealth inequality, could partly explain the decline in income inequality since 2008. The paper argues that since part of the reversal of these drivers is policy induced, it is important that the policy actions continue for income inequality to decline further. The paper further argues that a critical factor underlying the Kuznets hypothesis is that taxation and transfers play a bigger role in income redistribution as a country becomes more developed, while their role is still limited in the PRC, the future path of the country's income inequality may not be one directional; and reducing income inequality significantly may require personal income tax and transfers to play a greater role over time.
Keywords: D31; D63; N35; 330; income inequality; Kuznets hypothesis; the PRC economy